Composite thin film of simultaneously formed carbon and SnO2 QDs for supercapacitance application - Jadhav, Aarti; Patil, Sagar; Patil, Kashinath Rangu; Sathaye, Shivaram Dattatray; Rode, Chandrashekhar Vasant (New Journal of Chemistry, 2018)
Composite material with uniform size and structure is a critical asset that decides its properties like charge transfer, thermal, photoluminescence, mechanical, etc. and consequently the applications. Here for the first time, we report the concept of flame/combustion at liquid-liquid interface to synthesize in situ, thin film formation of composite consisting of two or more quantum dots. Synthesis of thin films of a composite containing C and SnO2 QDs having particle sizes below 3 nm was successfully done. As compared to a single quantum dots system, the formed composite showed significantly improved specific capacitance due to the synergistic effect arising from strong interaction between C and SnO2 QDs. This was confirmed by XPS, UV visible spectroscopy and photoluminescence spectra. Moreover, it was confirmed that even after 1000 charge/discharge cycles, the interaction between C and Sn remained unaltered; indicating significant stability of capacitance. Some of the advantages of this method include one step, eco-friendly process at ambient conditions. The generality of the method was established by synthesizing C-ZnO and C-TiO2 composite thin film. This new approach can be extended to form many other valuable composite thin films for various applications.